중국도입 배추 소포자배양에 의한 배가반수체의 종자생산능력 - 조만현(Man Hyun Jo); 함인기(In Ki Ham); 박민영(Min Young Park); 김태일(Tae Il Kim); 임용표(Yong Pyo Lim); 이은모(Eun Mo Lee) (Weon'ye gwahag gi'sulji, 2012)
A total of eleven Chinese cabbage accessions were used for microspore culture and were grown to take basal data. Based on the collected data, breeding materials were chosen to develop new improved Chinese cabbage cultivars. The range of microspore-derived embryoid taken from flower buds was 1.6 to 35.4 embryoids. The embryoids from IT26110 and IT26153 among the Chinese cabbages were more than 34 per flower bud. The viability rate after cold treatment was low from 0.2 to 11.7%. The range of fertility rate was 7.7 to 58.8% in general but the IT26118, IT26122, IT26128, IT26130, and IT26164 were more than 50%. The result of their seed production ability by selfing was 11.9 seeds per siliqua in IT26128 while the others were less than 10 seeds. In the microspore culture using parents of different hereditary, the number of embryoids, the number of plants, the rate of fertility and their pure seed production ability appeared to be very different in doubled haploid lines obtained from fertile plants of Chinese cabbage. 새로운 육종소재를 개발하고 신품종 육성에 이용할 수 있는 기초 자료를 얻고자, 중국도입 배추 11종의 소포자를 배양하여 식물체를 생산하였으며, 획득개체의 종자생산능력을 조사하였다. 화뢰당 획득 소포자유래배는 1.6-35.4개이었으며, 11품종 중 IT26110과 IT 26153만이 화뢰당 34개 이상의 소포자유래배를 얻을 수 있었다. 저온처리 후까지 생존한 식물체비율은 획득 소포자유래배 대비 0.2-11.7%로 낮았으며, 이들 식물체 중 임성개체 비율은 7.7-58.8%이었으나 IT26118, IT26122, IT26128, IT26130, 그리고 IT26164는 50% 이상이었다. 이들을 자식하여 종자생산능력을 조사한 결과 IT26128은 장각과당 11.9개의 채종하였으나 나머지 품종들은 10개 미만이었다. 이와 같이 유전적 기원이 다른 모본을 이용한 소포자배양을 할 때 배상체 획득수나, 소포자유래배에서 유도된 식물체수 및 임성개체 비율, 그리고 정립생산능력이 획득된 배가반수체 계통별로 큰 차이를 보였다.